Pentingnya Sumber Daya Manusia (SDM) dalam Pemasaran Pendidikan di Era Society 5.0 - Dedi Abu Samsudin; Abdul Mu’in; Anis Zohriah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research explores the role of Human Resources (HR) in education marketing in the Society 5.0 era, where HR has a crucial role in developing relevant and innovative marketing strategies. Using the qualitative research method of literature study, the research includes identifying key elements in the role of HR, determining scope boundaries, and selecting library sources through various trusted information sources. Analysis of findings was carried out using a thematic approach, organizing and analyzing findings from the literature to identify emerging patterns, trends and qualitative aspects. The research report compiles key concepts and a conceptual framework, detailing the role of HR in education marketing in the Society 5.0 era. It is hoped that this research will contribute to understanding the importance of human resources in the context of educational marketing which continues to develop.